Mass-radius constraints for the neutron star EoS - Bayesian analysis. (January 2016) - Ayriyan, A.; Alvarez-Castillo, D.E.; Blaschke, D.; Grigorian, H.
Abstract: We suggest a new Bayesian analysis (BA) using disjunct M-R constraints for extracting probability measures for cold, dense matter equations of state (EoS). One of the key issues of such an analysis is the question of a deconfinement transition in compact stars and whether it proceeds as a crossover or rather as a first order transition. We show by postulating results of not yet existing radius measurements for the known pulsars with a mass of 2Mq that a radius gap of about 3 km would clearly select an EoS with a strong first order phase transition as the most probably one. This would support the existence of a critical endpoint in the QCD phase diagram under scrutiny in present and upcoming heavy-ion collision experiments.